Hubungan Kontrol Diri dalam Penggunaan Sosial Media dengan Prokrastinasi Akademik pada Mahasiswa Tingkat Akhir - Shelvia Nurul Fahira; Isnaya Arina Hidayati (Fakultas Psikologi Universitas Pancasila, 2022)
The purpose of this study was to determine the relationship between self-control in the use of social media with academic procrastination for final-year students at one of private universities in Surakarta. The selection of 104 subjects of this study used a purposive sampling technique with the criteria of students who were taking thesis lectures at one of private universities in Surakarta and had social media. This study uses a quantitative correlation approach with hypothesis testing using Pearson's product moment correlation. Based on the data analysis, the p value <0.05 is 0,000, which means that H0 is rejected and Ha is accepted. So it can be said that there is a relationship between self-control in the use of social media with procrastination to do the final project for students at one of private universities in Surakarta. The results of the correlation coefficient (R) are known to be -0,626, which means that the strength of the correlation between self-control behavior and procrastination on students' final assignments can be said to be strong with a negative correlation direction.